Reduction in microbial infection risks from raw milk by Electron Beam Technology. (March 2020) - Ward, Lindsay R.; Van Schaik, Erin; Samuel, James; Pillai, Suresh D.
Abstract: Consuming raw milk can be risky because of the possible exposure to a variety of infectious microorganisms. We hypothesized that at low doses, electron beam (eBeam) processing is effective at inactivating pathogens in raw milk. The log reduction of background microbial populations and inoculated pathogens ( C. burnetii, C. jejuni, E . coli O157:H7, L. monocytogenes, and S. aureus) in raw milk was empirically determined. Risk assessment (β-Poisson models and exponential risk) models were utilized to quantify the infection risks associated with these pathogens. At 2.0 kGy dose, the background titers of aerobic and anaerobic microbial populations (8.06 × 10 4 and 2.89 × 10 3  CFU/mL respectively) in raw milk were reduced to below detectable limits, representing a 4 log and 3 log reduction of aerobic and anaerobic microorganisms respectively. At 2.0 kGy eBeam dose, significant reductions (between 13-logs and 28-logs) of raw milk-associated pathogens is achievable. Quantitative microbial risk assessment illustrated the significant reduction in infection risks (resulting from possible C. jejuni, E. coli O157:H7, or L. monocytogenes exposure) if raw milk is processed using eBeam technology. Without eBeam processing, ingestion of raw milk containing potentially ~40 CFU/mL ( L. monocytogenes ) or ~10 3  CFU/mL ( C. jejuni and E. coli O157:H7) would result in ~8/10, ~8/10, and ~10/10 infections from these pathogens respectively. However, if raw milk were eBeam processed at 2.0 kGy dose, the infection risks from consumption of such potentially contaminated raw milk samples will decrease significantly to approximately less than 1 person out of 9.7 million individuals. This study suggests that 2.0 kGy eBeam dose is effective for inactivating microbial pathogens in raw milk. Highlights: Consumption of raw milk is unfortunately increasing. Raw milk can harbor a variety of infectious microorganisms. 2.0 kGy eBeam dose achieves a significant reduction of raw milk associated pathogens. 2.0 kGy dose eBeam reduces infection risks from raw milk to less than 1 in 9.7 million persons.